Relationship of Length of Work and Nutritional Status with Work Fatigue at Gold Craftsmen - Nur Juliana; Firnasrudin Rahim; Hamzah B; Wa Ode Megasari (MIRACLE Journal Of Public Health, 2021)
The problem that often arises for workers in the industrial sector, including household industries such as gold craftsmen, is work fatigue. Data shows the prevalence of work fatigue in workers reaches from 10% to 40%. Gold craftsmen who are still working manually, working longer than 8 hours/day and having a body posture that is not ideal so they are at risk of experiencing work fatigue. This study aims to determine the relationship between length of work and nutritional status with work fatigue on gold craftsmen in Malimongan Village, Wajo District, Makassar City. This type of analytic observational research uses a cross sectional study approach, involving 30 gold craftsmen as respondents who were taken by simple random sampling. Collecting data using questionnaires, body scales and stature meters which are then analyzed using non-parametric methods with the Kruskal Wallis test. The results showed that the length of work 8 hours/day was 44,3%, normal nutritional status was 70% and work fatigue was 60%. Statistical analysis showed that there was a relationship between length of work and work fatigue for gold craftsmen (p-value=0,016) while nutritional status and work fatigue were obtained (p-value=0,311). In conclusion, it is known that there is a relationship between length of work and work fatigue, and there is no relationship between nutritional status and work fatigue in gold craftsmen.